UPAYA PENINGKATAN KINERJA APARATUR SIPIL NEGARA (STUDI DI PUSKESMAS DARU KECAMATAN KAO UTARA) - Koda, Sisilia; Rumapea, Patar; Tulusan, Femmy (Sam Ratulangi University, 2017)
This research aims to get the picture as a source of knowledge of the ASN in improving the performance of theservice of the quality of health services with consistent work time in Clinics Daru North HalmaheraRegency. As for the type of research useda qualitative approach and methods is descriptive. Descriptive methodof focus or emphasis on problems or phenomena that are found at the time of research that illustrates theempirical (fact). Informants in this study amounts to 10 people with key informants was the headof the clinic. Data collection techniques used are interviews and observations. The data collected isanalyzed using the interactive model from Miles and HubermanThe results showed that employee performance improvement efforts based on the quality of service so thatthe service conducted at the clinic as a benchmark. Program or duty committed employees even the processof implementation of the program can be run properly, among others, the implementation of theprogram outside of the building and outside the clinic. The quality of service provided to the community thatis the time the work was able to be Accounted for as an employee because in the process of employment allexist tupoksinya respectively.The research results show the performance of employees in the health centers has increased in quality From aquality service and a quality performance within and outside of the building and have reached theoptimal working standard, it is supportedwith a performance executed according the rules and goals.Keyword: Performance Improvement Effort, The Civil Authorities Of The State (ASN),Clinics Daru.